Indian species of Shirozuellini (Coleoptera: Coccinellidae), including a new species of Sasajiella Miyatake from Tamil Nadu - Poorani, J.; Thanigairaj, R. (Zootaxa, 2021)
The tribe Shirozuellini (Coleoptera: Coccinellidae) is represented by only four species in the Indian Subcontinent. The two species found in mainland India, Promecopharus andrewesi Sicard and Ghanius karachiensis Ahmad, are briefly reviewed: the species are diagnosed, key characters illustrated, and information provided on their distribution and hosts. The genus Sasajiella Miyatake (Coccinellidae: Shirozuellini), is reported for the first time from mainland India and a new species, Sasajiella boothi sp. n., collected from the state of Tamil Nadu, is described and illustrated. The male genitalia and larva of Sasajiella are illustrated for the first time. This is one of only five species in the tribe Shirozuellini known from the Indian subcontinent.